Towards sustainable energy and fuels from waste pathways for the UK - Vazquez-Peraita, Lola (2022)
Energy and Fuels from Municipal Solid Waste (MSW) and Commercial and Industrial (C&I) Waste can have an important role to play in the energy mix system and transition to the lower carbon economy towards the 2050 target. However, the co-existence of the Energy and Fuels from Waste (EfW) sector, the low carbon economy, and the circular economy (CE) are not obvious bedfellows. The EfW sector is seen by some stakeholders as an essential component of renewable energy policies, waste management policies and the development of sustainable integrated waste management systems. However, it also generates controversy among other stakeholders who see the sector as undermining the development of more sustainable waste management systems, the transition to a CE and lower carbon economy. Consequently, to date, there is still uncertainty about the long-term deployment strategy and role that the EfW sector can play in the national energy system and transition to a low carbon economy contributing towards UK net zero target by 2050. The aim of this thesis is to open up debate about the relative sustainability of six different EfW pathways; investigating the research question of ‘How can energy and fuels from waste (EfW) technologies (Incineration, Gasification and Anaerobic Digestion) be integrated and contribute towards sustainable waste management and energy systems in the UK?’.It does so by assessing and describing the perspectives and value-judgements of different stakeholders from UK Government departments, industry, academia and NGOs involved in the UK EfW sector. This research uses and further develops the elicitation approach called Multicriteria Mapping (MCM) to interview stakeholders, document and analyse their perspectives by gathering both qualitative and quantitative data around the relative sustainability of the six EfW pathways. The analysis brings to light the techno-economic, environmental, social and political uncertainties, divergent values and social priorities that shape the competing expectations of the sector and lead to differing conclusions about the sustainability and opportunities of waste management, EfW technologies and different energy outputs from EfW in the UK. The results show that there is potential for a symbiotic relationship between the EfW and waste management sectors and the CE, to help the UK achieve its net zero target by 2050. The thesis provides transparency on unresolved issues and existing barriers in the UK EfW sector, and on what the future opportunities of the EfW sector are according to the opinions of the stakeholder participants involved in the sector. A deeper understanding of these opportunities will lead to a better chance of EfW project deployment, and help the UK to develop a more sustainable and robust EfW sector, in line with sustainable waste management systems and the CE concept.